Preliminary Results of the Influence of the In Vivo Use of a Lymphatic Dye (Patent Blue V) in the Surgical Treatment of Crohn's Disease. (August 2014) - Tonelli, Pietro; Martellucci, Jacopo; Lucchese, Marcello; Comin, Camilla E.; Bergamini, Carlo; Pedica, Federica; Bargellini, Tatiana; Valeri, Andrea
Introduction . Recently, the lymphatic vessels has been considered to play a key role in the pathophysiology and, consequently, in the treatment of Crohn's disease (CD). The aim of this study is to show that the evaluation of lymphatic anomaly might be a useful tool in the recognition of the pathological involvement of the intestinal wall in CD. Material and methods . Fourteen patients with CD who underwent surgical treatment for distal ileum critical stenosis were prospectively evaluated. During surgery, 0.05 to 0.1 mL of Patent Blue V was injected into the subserosal layer of the antimesenteric edge of ileum and colon. The intestinal section was performed just beneath the outflow of the vital dye where it seemed to be normal (≤2 minutes), as a index of healthy intestinal wall. A comparison between the lymphatic alterations and the macroscopic aspects was performed. Results . Out of 14 patients, 13 were electively operated on, whereas 1 was treated in emergency. In 8 patients (57%), laparoscopic approach was chosen in the first instance. One patient needed laparotomic conversion. When comparing the Patent Blue V outflow time with the macroscopic and microscopic evidence of CD, we found an absolute integrity of the intestinal wall with an outflow ≤2 minutes. Mean follow-up was 110 months with a recurrence rate of 14%. Conclusion . We can conclude that this method may be of utility to distinguish between normal and diseased intestine in CD. The possible consequences in postsurgical recurrences of this evidence are critical.